Variety, Standing Crop and Net Community Productivity of the Vegetation on a Hard Ground and Stabilized Dunes Near Pilani, Rajasthan - Kumar, Arun (Annals of Arid Zone, 2016)
Variety, standing crop and net community productivity of the herbaceous vegetation have been evaluated on two sites near Pilani, Rajasthan. Variety ratio (species) individuals) increases progressively with the aging of community. The greatest growth of green biomass (dry weight of above ground living vegetation) and underground biomass occured in Augst-September which corresponds to the period of maximum rainfall. There was a considerable reduction in green biomass following maturity on the advent of dry season. Simultaneously there was a substantial depletion in the Underground biomass also. The turnover of underground biomass is very high, the value being 0.94. The total annual net community production on sites I and II are 370.75 and 83.57 g/m2/yr respectively and the corresponding rates of production on yearly basis are 101 and 0.20 g/m2/day on these two sites.